Advokasi Penerapan Kawasan Tanpa Rokok di Sekolah - Ulfa, Annisa Sayyidatul; Damayanti, Rita (UI Scholars Hub, 2021)
Background. Passive smokers in Indonesia reaches 75% or 96.9 million people. 66.2% students are exposed to cigarette in closed public spaces. Ministry of Education and Culture issued Permendikbud 64/2015 concerning KTR in the School Environment. implementation of KTR in schools still need optimization. Objective to see how the role of students in the advocacy process in implementing schools as smoke-free areas. Method. This research is a qualitative descriptive research with case study design conducted in a Junior High School of Bogor Regency. There were 7 informants. The data collection technique used Focus Group Discussion (FGD) and in-depth interviews by looking at the advocacy process using the